Inclusion of technology affinity in self scale–Development and evaluation of a single item measurement instrument for technology affinity - Henrich, Marvin; Kleespies, Matthias Winfried; Dierkes, Paul Wilhelm; Formella-Zimmermann, Sandra (Frontiers in Education, 2022)
The success of the increasing use of technology in education is highly dependent on learner acceptance. Although the Technology Acceptance Model (TAM) is dominant in research for surveying acceptance of technology, it does not allow the prediction of a successful first time use of technology. The successful first time use can be determined with the survey of technology affinity, as it corresponds to the expression of certain personality traits of users and is thus detached from the specific technology. Since there are no measurement instruments for the educational sector so far and existing instruments for measuring technology affinity do not meet the specific requirements for use in the educational context (e.g., limited time for questioning), we present the single item Inclusion of Technology Affinity in Self-Scale (ITAS). In study 1 we provide evidence of convergent and discriminant validity within the general population so that a generalization of its applicability is possible. In study 2 we subsequently tested ITAS in the actual target group, the educational sector. The high correlations of the ITAS with the ATI and the control instrument TA-EG (ranging from rs= 0.440 to rs= 0.679) show that ITAS is suitable for use in research. Furthermore, the newly developed instrument convinces with its low complexity, the graphical component, which requires little text understanding and the high time saving. This research thus can contribute to the investigation of technology affinity in the educational sector helping educators to conduct technical activities with their learning group, to predict possible difficulties and adjust their planning accordingly.